2021
DOI: 10.1063/5.0054327
|View full text |Cite
|
Sign up to set email alerts
|

Influence of solution electrical conductivity and ionic composition on the performance of a gas–liquid pulsed spark discharge reactor for water treatment

Abstract: The influence of solution electrical conductivity and ion composition on the performance of plasma reactors for water treatment applications is only partially understood. This study uses a point–point discharge over the surface of water in argon gas to determine the influence of solution conductivity, in the range of 0.3–45 mS/cm, on the physiochemical properties of spark discharges and the removal of two organic contaminants: perfluorooctanoic acid (PFOA) and Rhodamine B dye. The influence of various ions was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 62 publications
1
26
1
Order By: Relevance
“…Higher surface excess allows an increased probability for direct interaction with the gaseous electrons in the plasma above the interface. Similar findings were presented in a recent report, where an increase in the observed rate constant was measured due to higher surface accumulation with increasing solution conductivity …”
Section: Resultssupporting
confidence: 92%
“…Higher surface excess allows an increased probability for direct interaction with the gaseous electrons in the plasma above the interface. Similar findings were presented in a recent report, where an increase in the observed rate constant was measured due to higher surface accumulation with increasing solution conductivity …”
Section: Resultssupporting
confidence: 92%
“…A Spellman SL60PN1200 HV power supply was used with a custom-built circuit described in our previous work [15] to generate pulsed plasma in the bench-scale reactor. For the upscaled reactor, a TDK Lambda 102A-40kV-NEG power supply was used with a custom-build circuit shown in Figure S2.…”
Section: Electrical Circuitmentioning
confidence: 99%
“…It can be seen from SI Figure S4 that the change in the solution conductivity had a slight effect on the removal of PFOA. This observation is in accordance with Nau-Hix et al., finding that increasing conductivity exhibited a positive effect on the removal of PFOA in a point-to-point plasma reactor, and they attributed the increased removal to the salting out of PFOA (or other surfactant) to the plasma–liquid interface where the degradation occurs . These results indicated that the main effect of NO 3 – lies in the generation of RNS rather than the conductivity change.…”
Section: Resultsmentioning
confidence: 99%